Impact of Clinical Pathway and Rapid Direct Influenza Polymerase Chain Reaction Test Introduction on Readmissions Among Non-hospitalized Children with Influenza-Like Illness. (4th October 2017) - Chang, Yeh-Chung; Yuen, Stefanie; Shults, Justine; Cardenas, Ana Maria; Branas, Charles; Feemster, Kristen
Abstract: Background: Diagnosing influenza is challenging in children as influenza-like illness (ILI) symptoms are nonspecific. A clinical pathway was introduced in the emergency department (ED) of a large pediatric hospital to screen and treat patients at high risk of influenza-related complications. A new highly accurate, rapid polymerase chain reaction (PCR) influenza test was introduced the next year to provide more timely results. We aimed to measure the impact of the pathway and new PCR test on rates of all-cause ED readmissions and subsequent hospital admissions in all children with ILI discharged from the ED. Methods: We conducted a retrospective cohort study of non-hospitalized children≤18 years presenting to the ED with ILI over 3 winter seasons. ILI cases were identified using syndromic surveillance definitions. Outcomes included any return ED encounter or hospital admission within 2 weeks of initial ED visit. We compared difference in outcomes between the years before pathway introduction, after pathway introduction, and after rapid PCR test introduction. Multivariate logistic regression adjusted for pertinent sociodemographic and clinical covariates. Results: Among 10799 children with ILI, 6.1% had an ED readmission and 2.5% had a hospital admission within 2 weeks of an initial ED visit. Overall rates of ED readmission or hospitalization did not differ significantly by study year (5.7% vs 6.5% vs 6.1%, P = 0.41, and 2.9% vs 2.4% vs 2.3%, P = 0.36). In multivariate analysis, pathway introduction alone was not associated with likelihood of ED readmission or hospitalizations. However, rapid PCR test introduction with the pathway was associated with lower odds of hospitalization (aOR 0.70, 95% CI 0.51–0.97). High-risk status was associated with higher odds of ED readmission (aOR 1.42, 95% CI 1.21–1.68). High-risk status and severity of illness at the initial ED visit were associated with higher odds of hospitalization (aOR 1.51, 95% CI 1.13–2.03; aOR 10.66, 95% CI 6.05–18.79). Conclusion: Clinical pathway and rapid PCR test introduction does not decrease all-cause ED readmissions but does decrease all-cause hospital admissions in children with ILI. Clinical factors such as severity of illness and high-risk status play a large role in determining outcomes. Disclosures: All authors: No reported disclosures.